Non-Representational Geographies of Therapeutic Art Making : Thinking Through Practice - Boyd, Candice P. (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
Utilising non-representational theories and practice-led research methods, this book serves to reclaim therapeutics as ecological, spatial and material. It examines the sites and performances of a wide range of therapeutic art practices, including painting and drawing, dance movement therapy, fibre art, subterranean graffiti practice, and poetic permaculture. In doing so it provides an important assessment of the role and status of therapy in contemporary life. A highly interdisciplinary text, Boyd's research is informed by a thorough reading of post-structural theory including contemporary feminism, Guattari's ethico-aesthetic paradigm, Whitehead's process-oriented ontology, and Deleuze's writing on sense and the event. This innovative study will prove essential for scholars and practitioners of cultural geography, socially-engaged art, therapeutic studies, and occupational therapy. Candice Boyd is an artist-geographer with a background in clinical psychology. She is a Senior Fellow in the School of Geography, University of Melbourne, Australia. Her main research interests involve the geographies of mental health, cultures of sense and movement, therapeutic spaces, and contemporary museum geographies.
Keywords: Social sciences.; Historiography.; Occupational therapy.; Ethnography.; Sociology -- Research.; Human geography.; elektronické knihy; electronic books